2009
DOI: 10.1115/1.3070577
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wakes and Secondary Flow on Re-attachment of Turbine Exit Annular Diffuser Flow

Abstract: In this paper numerical results of wake and secondary flow interaction in diffuser flow fields are discussed. The wake and secondary flow are generated by a rotating wheel equipped with 30 cylindrical spokes with a diameter of 10 mm as a first approach to the turbine exit flow environment. The apex angle of the diffuser is chosen such that the flow is strongly separated according to the well-known performance charts of Sovran and Klomp (1967, “Experimentally Determined Optimum Geometries for Rectilinear Diffus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The ongoing increase in affordable computing power, made the analysis of unsteady, heterogeneous inflow conditions viable. Kluß et al showed by means of numerical simulations that unsteady wakes and secondary flow can lead to a rise of the pressure recovery of an annular diffuser above the values predicted by empirical design charts [5]. These findings were confirmed by simulations and measurements [6][7][8][9].…”
Section: Diffuser Researchmentioning
confidence: 87%
“…The ongoing increase in affordable computing power, made the analysis of unsteady, heterogeneous inflow conditions viable. Kluß et al showed by means of numerical simulations that unsteady wakes and secondary flow can lead to a rise of the pressure recovery of an annular diffuser above the values predicted by empirical design charts [5]. These findings were confirmed by simulations and measurements [6][7][8][9].…”
Section: Diffuser Researchmentioning
confidence: 87%
“…In addition to the static inlet conditions Kluß et al (2009) numerically investigated the effects of unsteady wakes and secondary flows shed from rotating cylindrical spokes upstream of the diffuser on the pressure recovery. In contrast to predictions made using diffuser design charts assuming static inlet conditions, the unsteady inflow caused a re-attachment of the boundary layer.…”
Section: Stabilisation Numbermentioning
confidence: 99%